ANALISIS PERSEPSI KONSUMEN TERHADAP KEINGINAN MENGGUNAKAN E-COMMERCE DALAM BERTRANSAKSI ONLINE - Fajar Sulaiman Noviandi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The desire to use is a desire or action taken by a consumer to determine a choice from several available alternatives to solve problems. The level of desire to use is closely related to the development of the electronic commerce (e-commerce) business. Factors that can effect the desire to use e-commerce in online transactions include consumer perceptions of ease and usefulness of e-commerce. This study aims to analyze consumer perceptions related to ease and usefulness of e-commerce, either partially or simultaneously on desire to use e-commerce in online transactions. The method used was descriptive method and quantitative method. The sample of this research was 97 people of early adults aged 20-30 years in Sumedang City. Data collection techniques used a questionnaire with data analysis through multiple linear regression. The results of statistical tests that ease had a positive and significant effect on desire to use e-commerce in online transactions; usefulness had a positive and significant effect on desire to use e-commerce in online transactions; ease and usefulness had a simultaneous and significant effect on desire to use e-commerce in online transactions.